2015
DOI: 10.1242/dev.120394
|View full text |Cite
|
Sign up to set email alerts
|

Progress and renewal in gustation: new insights into taste bud development

Abstract: The sense of taste, or gustation, is mediated by taste buds, which are housed in specialized taste papillae found in a stereotyped pattern on the surface of the tongue. Each bud, regardless of its location, is a collection of ∼100 cells that belong to at least five different functional classes, which transduce sweet, bitter, salt, sour and umami (the taste of glutamate) signals. Taste receptor cells harbor functional similarities to neurons but, like epithelial cells, are rapidly and continuously renewed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 157 publications
1
132
0
6
Order By: Relevance
“…Analogous to the crypt-villus organization of the small intestine, progenitors are thought to lie in the interpapillary epithelium (IPE), where they contribute to the renewal of three to four neighboring papillae (Okubo et al, 2009;Tanaka et al, 2013). Although much is known about the mechanisms that regulate taste bud development Barlow, 2015), comparatively little is known about how filiform papillae form.…”
Section: Oral Epithelial Development Is Diverse and Dynamicmentioning
confidence: 99%
“…Analogous to the crypt-villus organization of the small intestine, progenitors are thought to lie in the interpapillary epithelium (IPE), where they contribute to the renewal of three to four neighboring papillae (Okubo et al, 2009;Tanaka et al, 2013). Although much is known about the mechanisms that regulate taste bud development Barlow, 2015), comparatively little is known about how filiform papillae form.…”
Section: Oral Epithelial Development Is Diverse and Dynamicmentioning
confidence: 99%
“…Several elegant studies, mostly in mice, have shown that Wnt/β-catenin, Shh, Bmp and Fgf signalling are required for taste bud cell specification and patterning (e.g. Barlow, 2015;Barlow and Klein, 2015;Beites et al, 2009;Bloomquist et al, 2015;Gaillard et al, 2015;Iwatsuki et al, 2007;Kapsimali and Barlow, 2013;Kapsimali et al, 2011;Liu et al, 2007Liu et al, , 2013Petersen et al, 2011;Zhou et al, 2006 (Kuo and Krasnow, 2015;Noguchi et al, 2015). (B) In the case of taste buds, motile taste bud cells can have random, confined or directed motility relative to the centre of the mass of the organ.…”
Section: Taste Bud Formation: Getting Together In Many Waysmentioning
confidence: 99%
“…Mesenchyme and sensory neurons can provide additional signals, cells or innervation that contribute to induction, differentiation or patterning of the epithelium, thus complementing the capacity of the epithelial cells to construct the organ (i.e. Ahn, 2015;Barlow, 2015;Biggs and Mikkola, 2014;Hardy, 1992;Kapsimali and Barlow, 2013;Lee and Tumbar, 2012;Naveau et al, 2014;Pispa and Thesleff, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Наявність серед клітин нервового гребеня ссавців стовбурових клітин встановлена не-щодавно [13]. Стовбурові клітини нервового гребеня (СКНГ) дають початок численним клітинам нейраль-ного фенотипу -нейронам та глії чутливих вузлів, більшості черепних нервів (за винятком зорового, нюхового, ймовірно, присінково-завиткового) [14], елементам периферійної частини смакового (за ви-нятком сенсорних клітин [15]), нюхового [16] аналіза-торів (проте, не слухового [17]), гангліям вегетативної нервової системи, нейролемоцитам ПН тощо. Клітини мезенхімального («ектомезенхімального») фенотипу та структур, що утворюються з СКНГ, включають фібробласти ПН, кістки черепа, гладенькі міоцити артерій голови та шиї, перицити судин мозку, мозкові оболонки, клітини пульпи зуба та одонтобласти, клі-тини періодонтальної зв'язки та зубного сосочка, ади-поцити та клітини дерми обличчя, сполучнотканинні елементи залоз, м'язів та сухожиль голови, стромальні клітини рогівки, м'язи війчастого тіла.…”
Section: Abstract: Peripheral Nerve Injury; Autoneuroplasty; Tissue Eunclassified